Pyrimido[1″, 2″:1, 5]pyrazolo[3, 4-b]quinolines: Novel compounds that reverse ABCG2-mediated resistance in cancer cells. Issue 1 (28th June 2016) - Karthikeyan, Chandrabose; Malla, Ritu; Ashby, Charles R.; Amawi, Haneen; Abbott, Kodye L.; Moore, Joshua; Chen, Joel; Balch, Curt; Lee, Crystal; Flannery, Patrick C.; Trivedi, Piyush; Faridi, Jesika S.; et al.
Highlights: Novel plant-derived synthetic derivatives (IND) could reverse multidrug resistance. IND derivatives potentiate mitoxantrone, doxorubicin sensitivity in cancer cells. IND derivatives modulate ABCG2 transporter activity at substrate binding site. Abstract: Overexpression of ATP-binding cassette transporter (ABC) subfamily G2 in cancer cells is known to elicit a MDR phenotype, ultimately resulting in cancer chemotherapy failure. Here, we report, for the first time, the effect of eight novel pyrimido[1″, 2″:1, 5]pyrazolo[3, 4- b ]quinoline (IND) derivatives that inhibit ABCG2 transporter restoring cancer cell chemosensitivity. IND -4, -5, -6, -7, and -8, at 10 µM, and nilotinib at 5 µM, significantly potentiated (8–10 fold) the cytotoxicity of the ABCG2 substrates mitoxantrone (MX) and doxorubicin in HEK293 cells overexpressing ABCG2 transporter, MX (~14 fold) in MX-resistant NCI-H460/MX-20 small cell lung cancer, and of topotecan (~7 fold) in S1-M1-80 colon cancer cells which all stably expressing ABCG2. In contrast, cytotoxicity of cisplatin, which is not an ABCG2 substrate, was not altered. IND-5, -6, -7, and -8 significantly increased the accumulation of rhodamine-123 in multidrug resistant NCI-H460/MX-20 cells overexpressing ABCG2. Both IND-7 and -8, the most potent ABCG2 inhibitors, had the highest affinities for the binding sites of ABCG2 in modeling studies. In conclusion, the beneficial actions of new class of agents warrant further development as potential MDR reversal agents for clinical anticancer agents that suffer from ABCG2-mediated MDR insensitivity.